Efficacy of eimeriostatics in mixed course of eimeriosis and balantidiosis in piglets - Bohach О.; Bogach М. (Scientific Progress & Innovations, 2025)
Epizootic well-being of farms with regard to infectious and invasive diseases is a key criterion for the efficiency of any livestock industry. Intestinal parasites have a significant impact on the efficiency of pig farming. In recent years, protozoan invasions caused by Eimeria and Balantidia have become significantly widespread among pigs. Testing of antiprotozoal drugs and their new dosage forms is actively conducted both in Ukraine and abroad. However, the effectiveness of the same drug in the same dose may vary due to differences in testing methods, errors in result evaluation, and the emergence of resistant parasite strains. The developed drug Amprolev-plus showed 90 % effectiveness for eimeriosis and 100 % for cryptosporidiosis in calves, 100 % effectiveness for mixed isosporosis and cryptosporidiosis in piglets. One of the components of this complex drug is sulfadimezin, which is widely used in veterinary medicine for the treatment of infectious diseases caused by microorganisms sensitive to it, in particular balantidiosis in pigs. The effectiveness of Amprolev-plus and, for comparison, Brovitacoccid in mixed course of eimeria and balantidiosis in piglets was determined by the results of coproscopic studies before the use of the drugs and on days 7, 14 and 28 after treatment. Before the start of treatment, the intensity of Eimeria suis invasion in piglets of the experimental groups ranged from 27.1±0.9 to 27.9±2.3 oocysts in 10 fields of view of the microscope, while the number of Balantidium coli oocysts varied within 28.9±0.5 – 29.6±1.2 in 10 fields of view of the microscope. In piglets receiving Brovitacoccid, on the 14th day after treatment, 12.8±0.5 oocysts of E. suis and 19.9±0.2 oocysts of B. coli were recorded in 10 fields of view of the microscope. By the 28th day, E. suis oocysts were not recorded, and the intensity of B. coli infection decreased to 8.7±0.1 oocysts. In the second experimental group, where Amprolev-plus was used, on the 14th day after treatment, the number of E. suis oocysts was 14.5±0.3 in 10 fields of view of the microscope, and B. coli ‒ 3.9±0.1 in 10 fields of view of the microscope. On the 28th day after treatment, oocysts of both pathogens were not recorded. On the 28th day after treatment, the effectiveness of Amprolev-plus against the pathogens Eimeria suis and Balantidium coli was 100 %, which indicates its high antiparasitic activity in the case of mixed invasions, while Brovitacoccid showed 100 % effectiveness exclusively against eimeria, confirming its specific focus against eimeria in the same type of invasions, and only 66.7 % against balantidiosis.